1993
DOI: 10.1016/0735-1097(93)90791-x
|View full text |Cite
|
Sign up to set email alerts
|

Re-expansion of balloon-expandable stents after growth

Abstract: Re-expansion of intravascular stents is feasible after growth in juvenile swine without significant injury to neointima, media or adventitia. The results of this study support careful and selective use of intravascular stents as an adjunct to balloon dilation of congenital stenoses in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(38 citation statements)
references
References 15 publications
1
36
0
1
Order By: Relevance
“…Experimental studies have shown that stents implanted in the aorta become incorporated within the aortic wall and can be further expanded in growing animals [15,16]. More recently, several clinical studies have shown excellent immediate results in children and young adults with severe coarctation of the aorta [17][18][19].…”
Section: Introductionmentioning
confidence: 98%
“…Experimental studies have shown that stents implanted in the aorta become incorporated within the aortic wall and can be further expanded in growing animals [15,16]. More recently, several clinical studies have shown excellent immediate results in children and young adults with severe coarctation of the aorta [17][18][19].…”
Section: Introductionmentioning
confidence: 98%
“…Despite reasonably good short and long term results [74], some issues, such as restenosis, inability to address long, tubular coarctations, vessel rupture, and aneurysm formation, still remain. In addition, experimental work in animal models (75)(76)(77)(78)(79)(80)(81) has demonstrated feasibility and utility of stents in the management of coarctation. Consequently, stent therapy of coarctation has gained acceptance over the last two decades [15,50,.…”
Section: Coarctation Of the Aortamentioning
confidence: 99%
“…To address this question, Morrow et al [94] implanted stents in the aorta of growing swine and demonstrated the feasibility of reexpansion without significant injury to the neointima, the media, or adventitia. In an animal study, Mendelsohn et al [89] described aortic rupture after stent redilation in 2 of 7 animals.…”
Section: Endovascular Stenting and Coamentioning
confidence: 98%